Integrated Multi-Omics Profiling Identifies PDZ-Binding Kinase (PBK) as a Novel Prognostic Biomarker in Hepatocellular Carcinoma - Zhang J; Xu Y; Ni X; Mao Z; Xiao H; Chen M; Lin Y; Pan J; Zhang B; Zhang L; Zheng X; Song G; et al. (Journal of Hepatocellular Carcinoma)
Juan Zhang,1,* Yingyu Xu,2,* Xiaojian Ni,2,* Zhiyi Mao,3,* Haitao Xiao,4 Maopei Chen,1 Youpei Lin,5 Jiaomeng Pan,5 Boheng Zhang,6 Lan Zhang,1 Xueying Zheng,3 Guohe Song,5 Ningling Ge1 1Department of Hepatobiliary Oncology, Liver Cancer Institute, Zhongshan Hospital; Key Laboratory of Carcinogenesis and Cancer Invasion (Ministry of Education), Fudan University, Shanghai, People’s Republic of China; 2Department of Biliary Surgery, Zhongshan Hospital, Fudan University; Biliary Tract Disease Center of Zhongshan Hospital, Fudan University; Biliary Tract Disease Institute, Fudan University; Cancer Center, Zhongshan Hospital, Fudan University; Shanghai Biliary Tract Minimal Invasive Surgery and Materials Engineering Research Center, Shanghai, People’s Republic of China; 3Department of Biostatistics, Key Laboratory of Public Health Safety of Ministry of Education, School of Public Health, Fudan University, Shanghai, People’s Republic of China; 4Department of Traumatic Orthopedics, Hainan General Hospital, Haikou, People’s Republic of China; 5Department of Hepatobiliary Surgery and Liver Transplantation, Key Laboratory of Carcinogenesis and Cancer Invasion, Ministry of Education, Liver Cancer Institute, Zhongshan Hospital, Fudan University, Shanghai, People’s Republic of China; 6Department of Hepatobiliary Oncology, Zhongshan Hospital, Fudan University (Xiamen Branch), Xiamen Clinical Research Center for Cancer Therapy, Clinical Research Center for Precision medicine of abdominal tumor of Fujian Province, Xiamen City, Fujian Province, People’s Republic of China*These authors contributed equally to this workCorrespondence: Guohe Song, Email docsong2013@163.com Ningling Ge, Email ge.ningling@zs-hospital.sh.cnBackground: Hepatocellular carcinoma (HCC) necessitates novel immunotherapeutic targets. PBK, a cancer/testis antigen (CTA), was identified as a pivotal hub gene influencing prognosis, tumor mutation burden (TMB), and immune microenvironment remodeling.Methods: PBK was prioritized using weighted gene co-expression network analysis (WGCNA) and differential expression screening in the TCGA-LIHC cohort, intersected with curated CTAs. Analyses assessed correlations with clinicopathological features (TNM stage, survival), genomic characterization (mutation frequencies), and functional validation via siRNA-mediated PBK knockdown in Huh7 cells (migration assay). Single-cell RNA sequencing (scRNA-seq) profiled of the tumor immune microenvironment.Results: PBK overexpression was significantly correlated with advanced TNM stage (P < 0.05) and poor survival (log-rank P = 0.003). Genomic analysis revealed distinct mutation profiles: high-PBK tumors exhibited increased TP53 mutation frequency (39% vs 17%) but decreased CTNNB1 mutations (20% vs 31%). Patients exhibiting with combined PBK overexpression and high TMB demonstrated the poorest prognosis. Functional validation confirmed that PBK knockdown significantly inhibited Huh7 cell migration capacity (P < 0.05). scRNA-seq analysis showed PBK-enriched tumors contained elevated proportions of immunosuppressive SPP1(+) macrophages (22.33% vs 6.6%, FDR corrected P < 0.001) and CD8(+) SLC4A10(+) MAIT cells (9.82% vs 4.7%, FDR corrected P < 0.001).Conclusion: PBK synergistically drives HCC progression through three synergistic mechanisms: (1) promoting oncogenic mutation accumulation (eg, TP53), (2) increasing metastatic potential, and (3) reprogramming an immune-suppressive microenvironment enriched for SPP1(+) macrophages and CD8(+)SLC4A10(+) MAIT cells. This establishes PBK as a dual-purpose biomarker for prognostic stratification and immunotherapy resistance prediction, providing a mechanistic rationale for developing PBK-targeted therapies in HCC.Keywords: PDZ-binding kinase, bioinformatics, prognosis, cancer immunotherapy, hepatocellular carcinoma